Chapter Arte e meta-narrazione. Dalla produzione artistica ai modelli pedagogici personali, sociali e culturali - Belisario , Maria Laura (Studies on Adult Learning and Education, 2022)
The poster presented here collects data from the first year of a research aimed at investigating the models of thought that emerge from artistic performances from a point of view that is not only personal, but also social and cultural, in order to understand what art may tell us about the social and cultural contexts. A review of the literature has led to further investigate the concept of pedagogical model on the one hand and the potential of art from an educational point of view on the other. A pedagogical model is a model of thought that concerns attitudes and behaviors that guide the life of the individual and that is transmitted from generation to generation, from a personal, social and cultural point of view. These models are mainly manifested through symbolic language. Art gives life to a 'potential space' that allows the individual not only to become aware of his own representations of the world, but also to act concretely by transforming them. The study will then investigate the processes through which this happens, researching, through the words and narrations of the protagonists of the artistic experience, the models of thought emerging from the experience itself, and framing them within the social and cultural thought of reference. The methodology will be qualitative, with an eidetic approach and will adopt, as a strategy, the case study focused on the workshop of sound expression with natural objects called Orchestra della natura, managed by Daniele Delfino.